2016
DOI: 10.1371/journal.pone.0161527
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cinacalcet in Patients with Chronic Kidney Disease and Secondary Hyperparathyroidism Not Receiving Dialysis

Abstract: BackgroundSecondary hyperparathyroidism (SHPT) is a common complication in chronic kidney disease (CKD) patients. Cinacalcet could be a therapeutic option although its use is controversial in patients not receiving dialysis. Thus, the aim of this study is to assess the effectiveness and safety of cinacalcet in patients with CKD and SHPT without renal replacement treatment (RRT) and without renal transplantation (RT).MethodsA retrospective observational study was conducted. Patients were included if they had co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 27 publications
(54 reference statements)
2
14
1
1
Order By: Relevance
“…More worryingly, it increased phosphorus serum levels by 21.4% [8]. Similar or greater reductions in PTH levels were also observed in other clinical practice studies [10–16].…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…More worryingly, it increased phosphorus serum levels by 21.4% [8]. Similar or greater reductions in PTH levels were also observed in other clinical practice studies [10–16].…”
Section: Introductionsupporting
confidence: 67%
“…An analytical, retrospective, observational, non-placebo-controlled and multi-center lead-in study was conducted and previously reported elsewhere [10,11]. The lead-in study followed patients for up to 12 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cinacalcet, a calcimimetic agent, has been approved by the FDA to treat secondary hyperparathyroidism in dialysis patients. A recent observational study has shown beneficial effects of cinacalcet in lowering PTH, calcium and phosphate in non-dialysis CKD patients [111]. For patients with tertiary hyperparathyroidism (autonomous PTH production), therapeutic options are limited to cinacalcet or subtotal parathyroidectomy [112].…”
Section: Derangements Of Bone Mineral Metabolismmentioning
confidence: 99%
“…Secondary hyperparathyroidism is a common complication in dialysis patients, and can result in renal osteodystrophy, an increased risk of bone fractures, and a higher cardiovascular and overall mortality of patients . Reduced synthesis of calcitriol in the kidneys, hypocalcemia, and hyperphosphatemia commonly occur in development of secondary hyperparathyroidism . Active forms of vitamin D are used to treat secondary hyperparathyroidism in dialysis patients through binding with greater or lesser selectivity to vitamin D receptors distributed throughout the entire body .…”
mentioning
confidence: 99%